Pengelolaan Perkebunan Kelapa Sawit Berdasarkan Prinsip ISPO di PTPN VIII Cikasungka, Jawa Barat - Deilla Tsamrotul Fuadah; . Ernah (Jurnal Ilmu Pertanian Indonesia, 2018)
Indonesia is a major producer and exporter of palm oil in the world. The high demand of international market for environmentally friendly palm oil is the reason for Indonesian government to issue standard ISPO (Indonesian Sustainable Palm Oil) policy in 2011. ISPO is a standardization of oil palm plantation which aims to support the creation of environmentally friendly and sustainable palm oil products and mandatory for palm oil companies in Indonesia. Good management of oil palm plantations are those that comply with seven principles of ISPO. This research use some principles of ISPO, the first principles on the legality of the plantation business, the second principle of plantation management, and the fourth principle related to environmental monitoring and management. This study aims to determine the extent to which the application of plantation management in accordance with the criteria and the first, second, and fourth principle of ISPO in PTPN VIII Cikasungka. The research design used was qualitative descriptive with triangulation data collection techniques. The result of the research stated that PTPN VIII Cikasungka has been sufficiently suitable to manage plantation based on the first, second, and fourth principle of ISPO standard.